Moçambique pelo seu povo. Mozambique: Many People, Many Stories. Contested Masculinities & Gendered Perspectives - Penvenne, Jeanne Marie (Africana Studia, 2020)
This paper reflects on the scholarly contributions of José Capela, noting that, from his earliest publications, he anticipated and contributed to important and enduring themes in Mozambican History, and provided generations of students with innovative source material and avenues for investigation. Although it highlights Capela’s use of press sources, including the challenging working class newspapers of the early twentieth century, it focuses on his relationship with the press, especially Voz Africana, and his selection of late colonial era letters to the editor of that paper that he published in 1971 as Moçambique pelo seu povo. It argues that the collection is a treasury of vernacular, social and gender history. It provides a window into everyday life in Central Mozambique, young urban men’s development and deployment of social capital, examples of “writing upwards”, and men’s strategies to control women. It closes by seeking gendered perspectives through reading the contested masculinities discourses of the Voz Africana letters against oral narratives of urban working women focused on the same time period. Keywords: Vernacular history, Social Capital, Bridewealth (lobolo), Masculinities.